Asprosin May Play Important Roles in Spermatogenesis - Ozdede, Mehmet Ridvan; Oz, Zeynep Dila; Tektemur, Nalan Kaya; Gungor, Ibrahim Halil; Cakir, Aslihan; Turk, Gaffari; Kelestimur, Haluk (Wiley, 2023)
[Abstract Not Available]
Keywords: Asprosin; Sperm concentration; Morphology of sperm; Oligozoospermia.